2017
DOI: 10.1093/gbe/evx219
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Genetic Diversity among Cassava Bemisia tabaci Whiteflies Using NextRAD Sequencing

Abstract: Bemisia tabaci threatens production of cassava in Africa through vectoring viruses that cause cassava mosaic disease (CMD) and cassava brown streak disease (CBSD). B. tabaci sampled from cassava in eight countries in Africa were genotyped using NextRAD sequencing, and their phylogeny and population genetics were investigated using the resultant single nucleotide polymorphism (SNP) markers. SNP marker data and short sequences of mitochondrial DNA cytochrome oxidase I (mtCOI) obtained from the same insect were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
106
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(120 citation statements)
references
References 93 publications
10
106
4
Order By: Relevance
“…For example, NUMTs (nuclear mitochondrial sequences) have been misidentified and published in high frequencies 9 which resulted in conflicting estimates of inter-species nucleotide distances 2,10 and erroneous molecular species diagnosis (e.g., MEAM2, see Dinsdale et al 10 cf . Tay et al 11 ; SSA4 see Berry et al 12 and Wosula et al 13 cf . Elfekih et al 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, NUMTs (nuclear mitochondrial sequences) have been misidentified and published in high frequencies 9 which resulted in conflicting estimates of inter-species nucleotide distances 2,10 and erroneous molecular species diagnosis (e.g., MEAM2, see Dinsdale et al 10 cf . Tay et al 11 ; SSA4 see Berry et al 12 and Wosula et al 13 cf . Elfekih et al 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties to identify NUTMs and pseudogenes have significantly and negatively impacted research efforts to better manage the Bemisia cryptic species pest complex 25 , leading to misinterpretations of genome-wide SNP data 13 and understanding of evolutionary genomics involving whole genome sequencing 26 . Although the recently published mtCOI dataset with 513 B. tabaci sequences 8 aimed to address molecular diagnostic needs and species identification with efforts to remove insertion-deletion (indel)-affected sequences from the original dataset 8 , indel-affected sequences nevertheless remained present, while amino acid substitution patterns in sequences unaffected by indels were not examined.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques based on RADseq include original RAD, double‐digest RAD (ddRAD), type IIB endonucleases restriction site‐associated DNA (2b‐RAD), and ezRAD (Andrews, Good, Miller, Luikart, & Hohenlohe, ; Davey et al, ). In recent years, the RADseq technique has been widely used in the study of population genomics (Blanco‐Bercial & Bucklin, ; Wosula, Chen, Fei, & Legg, ), with the minimum sample size for population genomics being evaluated based on simulation (Willing et al, ) or empirical analysis (Nazareno et al, ). For example, by estimating the genetic differentiation ( F ST ) a simulation analysis has shown that sample size can be reduced to four to six individuals when using a large number of SNPs (Willing et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high-throughput sequencing technology, SNP markers have been widely used in genetic diversity and evolutionary analysis, high-density genetic linkage map construction, genomic association analysis, and QTL mapping (Brookes 1999, Fujii et al 2013). Simplified genome sequencing was proposed by Miller et al in 2007, and the corresponding technology of restriction endonuclease-related DNA sequencing (RAD-seq) was developed and became widely used in plant research including tea (Hua et al 2016), cassava (Wosula et al 2017), eggplant (Barchi et al 2011), sesame (Wang et al 2016), and barley (Chutimanitsakun et al 2011). It has also been used for fruit tree research such as apple (Sun et al 2015), pummelo (Guy et al 2015), and pear (Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%